Al-Qu’ran dan Islamic Entrepreneur: Abdurrahman Bin Auf - Abidah, Atik; Muhammad, Erfan; Bakri, Masykuri (El-Barka Journal of Islamic Economics and Business, 2022)
The purpose of this article is to analyze the behavior of the Islamic entrepreneur Abdurrahman ibn Auf based on the teaching of the Quran. Abdurrahman ibn Auf was an entrepeneur and a businessman who lived in the time of the Prophet. The clear-cut definition of entrepreneur term has not been found until now, so research on entrepreneurship remains relevant. The backbone of this study is the Quran, as it provides a deeper understanding based on what is contained in the Quran. Therefore, this article attempts to answer how is Abdurrahman ibn Auf’s manner in Islamic entrepreneur based on the study of the Quran? This research has to be done taking into account the fact that the current development of large corporations requires business research directly from the Quran for reference and facts about Islamic figures. This study uses library research methods and examines relevant scholarly articles as data sources. The results of this study contain a few basic verses about entrepreneurship. This verse is related to the attitude of business participants when conducting business. Finally, the concept of Islamic entrepreneur will be very suitable for application as it contains two meanings, Hablumminannas and Hablumminallah, as the attitude of Abdurrahman ibn Auf, who always adheres to the values in the verses of the QuranKarya tulis ini bertujuan untuk menganalisa perilaku Islamic Entrepeneur Abdurrahman bin Auf dalam kajian al-Qur’an. Abdurrahman bin Auf  merupakan seorang entrepreneur yang hidup pada zaman Rasulullah. Pemaknaan entrepeneur hingga detik ini belum menemukan istilah yang paling spesifik, sehingga kajian tentang entrepeneur masih relevan untuk dilakukan. Sandaran utama kajian ini adalah terhadap al-Qur’an, karena untuk memberikan pengertian yang jauh dan mendalam sesuai dengan apa yang terkadung di dalam al-Qur’an. Maka karya tulis ini berusaha menjawab pertanyaan bagaimana perilaku Islamic Entrepeneur Abdurrahman bin Auf dalam kajian al-Qur’an? Penelitian ini perlu dilakukan mengingat saat ini perkembangan usaha yang semakin besar akan membutuhkan kajian entrepeneur yang secara langsung diambil dari al-Qur’an sebagai rujukan serta spesifikasi terhadap seorang tokoh Islam. Penelitian ini menggunakan metode library research dan menelaah artikel ilmiah yang relevan sebagai sumber data. Hasil penelitian ini terdapat beberapa ayat dasar dalam berwirausaha. Ayat tersebut berkorelasi dengan sikap para pelaku usaha dalam menjalankan aktivitas usahanya. Pada akhirnya konsep wirausaha berbasis Islam akan sangat tepat untuk diterapkan, karena mengandung dua implikasi yakni hambumminannas dan hablumminallah, sebagaimana sikap Abdurrahman bin Auf yang senantiasa berpegang teguh terhadap nilai dalam ayat Al-Qur’an.